Dampak Ekonomi dari Ihtikar dan Siyasah Al-Ighraq dalam Konsep Jual Beli - Nuraini, Putri (UIR Press, 2019)
In Islam, the concept of buying and selling must be based on values ​​and ethics derived from the basic values ​​of religion that uphold honesty and justice. The existence of this discussion is related to the concept of buying and selling that is prohibited in Islam including ihtikâr and siyasa al-ighraq. Ihtikâr is the practice of hoarding goods so that the goods circulating in the community are reduced, then the price rises, which the hoarder has a large profit, while the community is disadvantaged. While siyasa al-ighraq (dumping/ price dropping) is a trading activity that aims to make a profit by selling goods at a price lower than the prevailing market price and in practice can lead to unhealthy competition and can disrupt the stability of market prices. In economics, the practice of ihtikâr and siyasa al-ighraq are often carried out by business actors in seizing economic markets, this will have an impact on the economy that is causing unhealthy competition and will ultimately result in disruption of market mechanisms. Therefore, Islam forbids the perpetrators of ihtikâr and siyasa al-ighraq and they belong to the category of buying and selling that is prohibited in Islam.